Metallic magnetic particles, metallic magnetic cores and inductors

JP7632719B2Active Publication Date: 2025-02-19MURATA MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024040263
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2025-02-19
Estimated Expiration
2040-03-27

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、絶縁性及び直流重畳特性に優れた金属磁性粒子及びインダクタ、絶縁性及び直流重畳特性に優れた金属磁性粒子を得ることのできる金属磁性粒子の製造方法、並びに、絶縁性及び直流重畳特性に優れた金属磁性体コアを得ることのできる金属磁性体コアの製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632719000002
    Figure 0007632719000002
  • Figure 0007632719000003
    Figure 0007632719000003
  • Figure 0007632719000004
    Figure 0007632719000004
Patent Text Reader

Abstract

To provide: a metal magnetic particle and an inductor that have excellent insulation properties and direct-current superposition characteristics; a method for manufacturing a metal magnetic particle capable of obtaining a metal magnetic particle having excellent insulation properties and direct-current superposition characteristics; and a method for manufacturing a metal magnetic core capable of obtaining a metal magnetic core having excellent insulation properties and direct-current superposition characteristics.SOLUTION: A metal magnetic particle (1) is provided with an oxide layer on a surface of an alloy particle (10) containing Fe and Si. The oxide layer has a first oxide layer (20), a second oxide layer (30), a third oxide layer (40) and a fourth oxide layer (50) from a side of the alloy particle. In line analysis of element content by using a scanning transmission electron microscope-energy dispersive X-ray spectroscopy, the first oxide layer (20) is a layer where Si content takes a local maximum value, the second oxide layer (30) is a layer where Fe content takes a local maximum value, the third oxide layer (40) is a layer where Si content takes a local maximum value, and the fourth oxide layer (50) is a layer where Fe content takes a local maximum value.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a metal magnetic particle, an inductor, a method for manufacturing a metal magnetic particle, and a method for manufacturing a metal magnetic core. [Background technology]

[0002] Power inductors used in power supply circuits are required to be compact, have low loss, and be compatible with large currents, and to meet these requirements, the use of metal magnetic particles with high saturation magnetic flux density as the magnetic material has been considered. Metal magnetic particles have the advantage of having a high saturation magnetic flux density, but the insulation resistance of the material alone is low, so in order to use them as magnetic bodies in electronic components, it is necessary to ensure insulation between the metal magnetic particles. For this reason, various methods for improving the insulation of metal magnetic particles have been considered.

[0003] For example, Patent Document 1 discloses a method for coating the surfaces of metal magnetic particles with an insulating film such as glass, and Patent Document 2 discloses a method for forming an oxide layer derived from the material on the surfaces of metal magnetic particles. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5082002 [Patent Document 2] Patent No. 4866971 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the method described in Patent Document 1 had the problem that it was not possible to form an insulating film such as glass uniformly on the surface of the metal magnetic particles, and that areas with a thin film thickness became the starting points of dielectric breakdown. In addition, the method described in Patent Document 2 has a problem in that the oxide layer derived from the raw material potentially contains defects, resulting in insufficient insulation reliability. Also, the metal magnetic material described in Patent Document 2 has a problem in that it cannot be heat-treated at a high temperature to prevent the oxidation of the raw material particles from progressing.

[0006] The present invention aims to provide metal magnetic particles and inductors with excellent insulation and DC superposition characteristics, a method for manufacturing metal magnetic particles that can obtain metal magnetic particles with excellent insulation and DC superposition characteristics, and a method for manufacturing metal magnetic cores that can obtain metal magnetic cores with excellent insulation and DC superposition characteristics. [Means for solving the problem]

[0007] The metal magnetic particle of the present invention is a metal magnetic particle having an oxide layer provided on the surface of an alloy particle containing Fe and Si, the oxide layer having, from the alloy particle side, a first oxide layer, a second oxide layer, a third oxide layer, and a fourth oxide layer, and in a line analysis of element content using a scanning transmission electron microscope-energy dispersive X-ray analysis, the first oxide layer is a layer in which the Si amount has a maximum value, the second oxide layer is a layer in which the Fe amount has a maximum value, the third oxide layer is a layer in which the Si amount has a maximum value, and the fourth oxide layer is a layer in which the Fe amount has a maximum value.

[0008] The inductor of the present invention is characterized by comprising the metal magnetic particles of the present invention.

[0009] The method for producing metal magnetic particles of the present invention includes the steps of: mixing raw material particles having an Si oxide film and an Fe oxide film on the surface of an alloy particle containing Fe and Si from the alloy particle side with a Si alkoxide and an alcohol; hydrolyzing and drying the Si alkoxide to form coated film-forming particles having a coating film containing silicon oxide formed thereon; and heat-treating the coated film-forming particles in an oxidizing atmosphere to form an oxide layer on the surface of the alloy particle, wherein the average thickness of the coating film is 10 nm or more and 14 nm or less.

[0010] The method for manufacturing a metal magnetic core of the present invention includes the steps of: mixing raw material particles having an Si oxide film and an Fe oxide film on the surface of an alloy particle containing Fe and Si from the alloy particle side with a Si alkoxide and an alcohol; hydrolyzing and drying the Si alkoxide to form coated film-forming particles having a coating film containing silicon oxide formed thereon; shaping the coated film-forming particles; and heat-treating a molded body of the coated film-forming particles in an oxidizing atmosphere to form an oxide layer on the surface of the alloy particle, wherein the average thickness of the coating film is 10 nm or more and 14 nm or less. Effect of the Invention

[0011] According to the present invention, it is possible to provide metal magnetic particles and inductors with excellent insulation and DC superposition characteristics, a method for manufacturing metal magnetic particles that can obtain metal magnetic particles with excellent insulation and DC superposition characteristics, and a method for manufacturing metal magnetic cores that can obtain metal magnetic cores with excellent insulation and DC superposition characteristics. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic diagram of an example of a metal magnetic particle of the present invention. [Diagram 2] FIG. 2 is a STEM image of Example 1. [Diagram 3] FIG. 3 is a diagram showing the results of the line analysis in Example 1. [Figure 4] FIG. 4 is a graph showing the relationship between the DC magnetic field Hsat@-20% [kA / m] (vertical axis) and the relative permeability (horizontal axis) at which the relative permeability value becomes 80% or less of the initial value in each of the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The metal magnetic particles, inductors, methods for producing metal magnetic particles, and methods for producing metal magnetic cores of the present invention will be described below. However, the present invention is not limited to the following configurations, and can be appropriately modified and applied within the scope of the present invention. Note that the present invention also includes a combination of two or more of the preferred configurations of the present invention described below.

[0014] [Metal magnetic particles] The metal magnetic particle of the present invention is a metal magnetic particle having an oxide layer provided on the surface of an alloy particle containing Fe and Si, the oxide layer having, from the alloy particle side, a first oxide layer, a second oxide layer, a third oxide layer, and a fourth oxide layer, and in a line analysis of element content using a scanning transmission electron microscope-energy dispersive X-ray analysis, the first oxide layer is a layer in which the Si amount has a maximum value, the second oxide layer is a layer in which the Fe amount has a maximum value, the third oxide layer is a layer in which the Si amount has a maximum value, and the fourth oxide layer is a layer in which the Fe amount has a maximum value.

[0015] FIG. 1 is a cross-sectional view showing a schematic diagram of an example of a metal magnetic particle of the present invention. As shown in FIG. 1, metal magnetic particle 1 has an oxide layer provided on the surface of alloy particle 10 containing Fe and Si. The oxide layers are, from the alloy particle 10 side, a first oxide layer 20, a second oxide layer 30, a third oxide layer 40 and a fourth oxide layer 50.

[0016] The alloy particles include Fe and Si. The weight ratio of Si in the alloy particles is preferably 1.5 parts by weight or more and 8.0 parts by weight or less per 100 parts by weight of the total weight of Fe and Si. If the weight ratio of Si in the alloy particles is less than 1.5 parts by weight, the effect of improving the soft magnetic properties is small, whereas if the weight ratio of Si in the alloy particles is more than 8.0 parts by weight, the saturation magnetization is significantly reduced and the DC bias characteristics are degraded.

[0017] The alloy particles may contain Cr in addition to Fe and Si. The alloy particles preferably contain less than 1.0 part by weight of Cr per 100 parts by weight of the total weight of Fe and Si, more preferably contain 0.9 parts by weight or less of Cr, and even more preferably contain no Cr. A low Cr content improves the saturation magnetic flux density, thereby improving the DC bias characteristics.

[0018] The alloy particles may also contain, as impurity components, the same elements as the impurities contained in pure iron. Examples of impurity components include C, Mn, P, S, Cu, and Al.

[0019] The oxide layer has, from the alloy particle side, a first oxide layer, a second oxide layer, a third oxide layer and a fourth oxide layer. In this specification, the oxide layer refers to a layer in which oxygen and metal elements (metal elements here include silicon (Si)) are both counted in the line analysis of element content described below. When oxygen and silicon are both counted, it is considered that an oxide containing silicon is present, and when oxygen and iron (Fe) are both counted, it is considered that an oxide containing iron is present.

[0020] The first oxide layer is a layer in which the amount of Si is maximum in a line analysis of element contents using a scanning transmission electron microscope (STEM)-energy dispersive X-ray analysis (EDX) (hereinafter simply referred to as line analysis). The second oxide layer is a layer in which the amount of Fe is maximum in the line analysis. The third oxide layer is a layer in which the amount of Si is maximum in the line analysis. The fourth oxide layer is a layer in which the amount of Fe is maximum in the line analysis.

[0021] The boundaries of the first oxide layer, the second oxide layer, the third oxide layer and the fourth oxide layer are defined as follows. The first oxide layer is defined as the region from the point where the Fe content and the Si content are reversed (first boundary) to the midpoint between the point where the Si content is maximized and the point where the Fe content is maximized (second boundary) in the line analysis of the element content using STEM-EDX. The second oxide layer is defined as the region from the second boundary to the midpoint (third boundary) between the point where the Fe content is at its maximum and the point where the Si content is at its maximum in a line analysis of the elemental content using STEM-EDX. The third oxide layer is defined as the region from the third boundary to the midpoint (fourth boundary) between the point where the Si content is at its maximum and the point where the Fe content is at its maximum in the line analysis of the element content using STEM-EDX. The fourth oxide layer is defined as the region from the fourth boundary in the line analysis of the element content using STEM-EDX to the point (fifth boundary) where the O amount (oxygen amount) in the line analysis is 34% of the maximum value.

[0022] In addition, the "amount" of each element in line analysis of element content using STEM-EDX refers to the number of X-ray counts specific to each element (also called net count), and does not indicate the weight ratio or atomic ratio. The magnification in STEM-EDX is set to 400,000 times.

[0023] The thickness of the first oxide layer is preferably 3.0 nm or more and 10 nm or less, and more preferably 4.0 nm or more and 7.0 nm or less. In a line analysis of element content using STEM-EDX, at the point where the Si content in the first oxide layer is at its maximum, the ratio of the Fe content to the Si content (Fe content / Si content) is preferably 0.10 or more and 0.30 or less, and more preferably 0.14 or more and 0.20 or less.

[0024] The thickness of the second oxide layer is preferably 3.0 nm or more and 8.0 nm or less, and more preferably 4.0 nm or more and 7.0 nm or less. In a line analysis of element content using STEM-EDX, at the point where the Fe amount in the second oxide layer is at its maximum, the ratio of the Fe amount to the Si amount (Fe amount / Si amount) is preferably 9.0 or more and 13 or less, and more preferably 10 or more and 12 or less.

[0025] The thickness of the third oxide layer is preferably 2.5 nm or more and 8.0 nm or less, and more preferably 3.5 nm or more and 6.0 nm or less. In a line analysis of element contents using STEM-EDX, at the point where the Si content in the third oxide layer is at its maximum, the ratio of the Fe content to the Si content (Fe content / Si content) is preferably 1.0 or more and 2.0 or less, and more preferably 1.4 or more and 1.8 or less.

[0026] The thickness of the fourth oxide layer is preferably 4.0 nm or more and 10 nm or less, and more preferably 5.0 nm or more and 7.5 nm or less. In a line analysis of the element content using STEM-EDX, at the point where the Fe amount in the fourth oxide layer is at its maximum, the ratio of the Fe amount to the Si amount (Fe amount / Si amount) is preferably 23 or more and 28 or less, and more preferably 24 or more and 26 or less.

[0027] The thicknesses of the first oxide layer, the second oxide layer, the third oxide layer, and the fourth oxide layer are determined by line analysis of three locations that divide the circumference of the metal magnetic particle into thirds in an enlarged image of the cross section of the metal magnetic particle observed by STEM-EDX, and the average thickness of each layer is determined. Similarly, the ratio of the Fe content to the Si content in each layer (Fe content / Si content) is determined by the average value of the measured values ​​obtained by line analysis of the three locations.

[0028] In the metal magnetic particles of the present invention, adjacent oxide layers preferably have different crystallinity. For example, when the first oxide layer is amorphous, the second oxide layer is preferably crystalline, the third oxide layer is preferably amorphous, and the fourth oxide layer is preferably crystalline. By joining an amorphous oxide layer and a crystalline oxide layer, the electrical resistance at the joining interface increases, so if the crystallinity of adjacent layers is different, the insulation resistance can be increased.

[0029] The crystallinity of each layer can be confirmed by whether or not periodic light and dark patterns appear in the FFT image, which is a Fourier transform of the STEM image. If the material is crystalline, periodic light and dark patterns will appear in the FFT image, and if the material is amorphous, periodic light and dark patterns will not appear in the FFT image.

[0030] [Inductor] The inductor of the present invention is characterized by comprising the metal magnetic particles of the present invention.

[0031] The inductor of the present invention includes the metal magnetic particles of the present invention, and therefore has high voltage resistance and excellent DC bias characteristics.

[0032] An inductor of the present invention comprises, for example, metal magnetic particles of the present invention and a winding disposed around the metal magnetic particles. The material, wire diameter, number of turns, etc. of the winding wire are not particularly limited and may be selected according to the desired characteristics.

[0033] The metal magnetic particles constituting the inductor of the present invention may be formed into a predetermined shape. Metal magnetic particles formed into a predetermined shape are also called metal magnetic cores. Therefore, an inductor consisting of a metal magnetic core made of the metal magnetic particles of the present invention and a winding arranged around the metal magnetic core is also an inductor of the present invention.

[0034] [Method of manufacturing metal magnetic particles] The method for producing metal magnetic particles of the present invention includes the steps of: mixing raw material particles having an Si oxide film and an Fe oxide film on the surface of an alloy particle containing Fe and Si from the alloy particle side with a Si alkoxide and an alcohol; hydrolyzing and drying the Si alkoxide to form coated film-forming particles having a coating film containing silicon oxide formed thereon; and heat-treating the coated film-forming particles in an oxidizing atmosphere to form an oxide layer on the surface of the alloy particle, wherein the average thickness of the coating film is 10 nm or more and 14 nm or less.

[0035] In the method for producing metal magnetic particles of the present invention, a coating film containing silicon oxide is formed on the surface of raw material particles having an Si oxide film and an Fe oxide film on the surface of the alloy particle, and the resulting material is heat-treated in an oxidizing atmosphere. It is believed that this results in the Si oxide film becoming the first oxide layer, the Fe oxide film becoming the second oxide layer, and the coating film becoming the third oxide layer. It is believed that the Fe in the Fe oxide film further diffuses out of the coating film and is oxidized, forming a fourth oxide layer containing Fe. For this reason, the metal magnetic particles of the present invention can be obtained by using the method for producing metal magnetic particles of the present invention.

[0036] In order to obtain a third oxide layer distinct from the second and fourth oxide layers, the average thickness of the coating film is preferably 10 nm or more. On the other hand, if the average thickness of the coating film is 14 nm or less, the Fe in the Fe oxide film is likely to diffuse out of the coating film, and the fourth oxide layer can be easily formed.

[0037] [Step of mixing raw material particles with Si alkoxide and alcohol] First, raw material particles containing Fe and Si are prepared, each having a Si oxide film and an Fe oxide film on the surface of the alloy particle from the alloy particle side. The method for forming the Si oxide film and the Fe oxide film on the surface of the alloy particles is not particularly limited, but may be a method in which fine particles of an FeSi alloy obtained by a water atomization method or the like are gradually oxidized. The gradual oxidation is a treatment in which the surface of the alloy particles is deliberately oxidized for the purpose of suppressing excessive oxidation of the alloy particles, thereby forming a surface oxide film that functions as a protective film against oxidation. For example, FeSi alloy particles are placed in a non-oxidizing atmosphere and dried, and the oxygen concentration in the atmosphere is gradually increased to gradually oxidize the surfaces of the FeSi alloy particles, forming Si oxide films and Fe oxide films on the surfaces of the alloy particles.

[0038] The alloy particles used in the method for producing metal magnetic particles of the present invention contain Si and Fe. The average particle size of the raw material particles is not particularly limited, but it is preferable that D50 is 1 μm or more and 10 μm or less. Here, D50 is the particle size at which the cumulative volume of the alloy particles is 50% as measured by a laser diffraction method.

[0039] Next, the raw material particles are mixed with Si alkoxide and alcohol.

[0040] The Si alkoxide is preferably tetraethoxysilane. When the silicon alkoxide is tetraethoxysilane, a coating film of uniform thickness is easily formed on the surface of the raw material particles. The alcohol is preferably ethanol.

[0041] When mixing the raw material particles with the Si alkoxide and alcohol, it is preferable to add polyvinylpyrrolidone as a water-soluble polymer. It is also preferable to add an aqueous ammonia solution as a basic catalyst. The Si alkoxide is easily hydrolyzed in the presence of a basic catalyst and water.

[0042] [Step of forming coated particles] Next, the Si alkoxide is hydrolyzed and dried to produce coated particles having a coating film containing silicon oxide formed thereon.

[0043] At this time, the average thickness of the coating film provided on the surface of the raw material particles is set to 10 nm or more and 14 nm or less.

[0044] [Step of Heat Treating the Coated Particles] The coated particles are then heat treated in an oxidizing atmosphere to form an oxide layer on the surface of the alloy particles.

[0045] The temperature of the heat treatment is preferably 600°C or higher and 740°C or lower. If the heat treatment temperature is less than 600°C, the Fe in the Fe oxide film may not diffuse to the outside of the coating film, whereas if the heat treatment temperature is more than 740°C, the oxidation reaction of the alloy particles may proceed, resulting in deterioration of the magnetic properties.

[0046] [Metal magnetic core manufacturing method] The method for manufacturing a metal magnetic core of the present invention includes the steps of: mixing raw material particles having an Si oxide film and an Fe oxide film on the surface of an alloy particle containing Fe and Si from the alloy particle side with a Si alkoxide and an alcohol; hydrolyzing and drying the Si alkoxide to form coated film-forming particles having a coating film containing silicon oxide formed thereon; shaping the coated film-forming particles; and heat-treating a molded body of the coated film-forming particles in an oxidizing atmosphere to form an oxide layer on the surface of the alloy particle, wherein the average thickness of the coating film is 10 nm or more and 14 nm or less.

[0047] In the method for producing a metal magnetic core of the present invention, a coating film containing silicon oxide is formed on the surface of raw material particles having a Si oxide film and an Fe oxide film from the alloy particle side, and the resulting coated film-formed particles are molded into a compact, which is then heat-treated in an oxidizing atmosphere to diffuse the Fe oxide film to the outside of the coating film to form a fourth oxide layer, as in the method for producing a metal magnetic particle of the present invention. Also, a metal magnetic core in which alloy particles are bonded to each other by oxide layers can be obtained.

[0048] Of the steps constituting the method for producing a metal magnetic core of the present invention, the steps other than the molding step are common to the method for producing a metal magnetic particle of the present invention.

[0049] In the molding process, the binder resin, the solvent, and the coated film-forming particles may be mixed and then the solvent may be removed to produce a granulated powder, which may then be molded, or the mixture of the binder resin, the solvent, and the coated film-forming particles may be directly molded. As the binder resin, epoxy resin, silicone resin, phenol resin, polyamide resin, polyimide resin, polyphenylene sulfide resin, ethyl cellulose, etc. are preferable. Examples of the solvent include an aqueous polyvinyl alcohol solution and terpineol.

[0050] The shape of the green compact produced in the molding step preferably corresponds to the shape of the desired metal magnetic core. The metal magnetic core may be, for example, rod-shaped, cylindrical, ring-shaped, rectangular, or the like.

[0051] The molding pressure in the molding step is not particularly limited, but is preferably 100 MPa or more and 700 MPa or less.

[0052] In the method for producing a metal magnetic core of the present invention, the molding step preferably includes a step of laminating and pressing green sheets containing the coating film-forming particles. When the molding process includes a step of stacking and pressing green sheets containing coating film-forming particles, the distance between the alloy particles becomes short in the molded body before heat treatment, making it easier to obtain a metal magnetic core in which the alloy particles are bonded to each other by an oxide layer.

[0053] A green sheet containing the coated film-forming particles can be obtained, for example, by mixing a solvent containing a binder resin with the coated film-forming particles to prepare a slurry, forming the slurry into a thin film by a doctor blade method or the like, and then removing the solvent. As the binder resin and the solvent, the same ones as those used when preparing the granulated powder can be suitably used.

[0054] A coil pattern or a part thereof may be formed on the green sheet containing the coating film forming particles using a conductive paste or the like.

[0055] The forming step may also include a step of printing and drying a paste containing the coating film-forming particles. EXAMPLES

[0056] The following examples more specifically disclose the metal magnetic particles, inductors, manufacturing methods of metal magnetic particles, metal magnetic cores, and manufacturing methods of metal magnetic cores of the present invention. Note that the present invention is not limited to these examples.

[0057] Example 1 FeSi alloy particles with a weight ratio of Fe:Si=93.5:6.5 were obtained by water atomization. The surface of the obtained FeSi alloy was observed by STEM, and it was confirmed that two oxide layers with an average thickness of about 10 nm were formed on the surface of the FeSi alloy particles. Using XPS analysis, elemental analysis was performed from the surface of the FeSi alloy particles in the depth direction, and it was confirmed that there is a layer containing Fe on the surface side of the FeSi alloy particles, and a layer containing Si inside that. From the above, it was confirmed that a silicon oxide film having an average thickness of about 10 nm and an iron oxide film having an average thickness of about 10 nm were formed on the surface of the FeSi alloy particles. The obtained FeSi alloy particles were used as raw material particles.

[0058] Polyvinylpyrrolidone K30 was added to ethanol containing the ammonia solution and FeSi alloy particles, and the mixture was stirred to obtain a mixed solution. Tetraethoxysilane was added dropwise to the resulting mixed solution, and the mixture was stirred for 60 minutes to obtain a slurry. The slurry was filtered, washed with acetone, and then dried at 60°C to obtain coated particles. After embedding the coated particles in resin, the cross section was polished and processed into thin slices using a focused ion beam (FIB) [SII SMI3050SE] to prepare samples for STEM observation. These samples for STEM observation were observed at approximately 400,000 magnifications using a STEM (Hitachi High-Technologies HD-2300A), and it was confirmed that the average thickness of the coated film was approximately 11 nm.

[0059] 100 parts by weight of the obtained coated particles were mixed with 6 parts by weight of epoxy resin and an aqueous polyvinyl alcohol solution, dried, and sieved to obtain a granulated powder. The granulated powder was filled into a doughnut-shaped mold with an outer diameter of 20 mm and an inner diameter of 10 mm, and the mold was pressurized at 60° C. and a pressure of 500 MPa for 10 seconds to form the coated particles into a ring shape with an outer diameter of about 20 mm, an inner diameter of about 10 mm, and a thickness of about 2 mm.

[0060] The obtained ring was degreased and sintered in a sintering furnace to obtain a sintered body (metal magnetic core) of metal magnetic particles. Degreasing was performed in air, and the temperature was raised to 400°C at a heating rate of 40°C / h, held for 30 minutes, and then naturally cooled. Firing was performed in air, and the temperature was raised to a peak temperature of 690°C in 40 minutes, held for 20 minutes, and then naturally cooled. Three rings were produced, one for STEM-EDX measurement, one for voltage resistance measurement, and one for relative permeability and DC superposition characteristics measurement.

[0061] [Line analysis by STEM-EDX] The obtained ring was embedded in resin, and the cross section was polished and processed by FIB to make a thin section to prepare a sample for STEM observation. Line analysis of the sample for STEM measurement was performed using STEM and EDX (EDAX GENESIS XM4). The starting point was the inside of the alloy particle, and elemental analysis was performed toward the outside (oxide layer). The magnification of STEM was 400,000 times. The STEM image is shown in Figure 2, and the results of the line analysis are shown in Figure 3. The vertical axis is the count number [arbitrary unit] of the characteristic X-ray (K line) of each element, and the horizontal axis is the distance [nm] from the starting point. The horizontal axis was measured at intervals of 0.9 nm or less.

[0062] From FIG. 2, it was confirmed that the first oxide layer 20, the second oxide layer 30, the third oxide layer 40 and the fourth oxide layer 50 were arranged in this order on the surface of the alloy particle 10. In addition, it was also possible to confirm from the STEM images that the alloy particles were bonded to each other via the first oxide layer, the second oxide layer, the third oxide layer, or the fourth oxide layer.

[0063] From FIG. 3, the thickness of the first oxide layer was 5.5 nm, the thickness of the second oxide layer was 4.9 nm, the thickness of the third oxide layer was 4.1 nm, and the thickness of the fourth oxide layer was 6.2 nm.

[0064] 3, it was confirmed that the oxide layer had a first oxide layer 20 in which the Si content was a maximum, a second oxide layer 30 in which the Fe content was a maximum, a third oxide layer 40 in which the Si content was a maximum, and a fourth oxide layer 50 in which the Fe content was a maximum. It was also confirmed that the alloy particles and the oxide layer contained almost no Cr. The ratio of the amount of Fe to the amount of Si (Fe amount / Si amount) at the point where the Si amount in the first oxide layer was maximum was 0.16. The ratio of the amount of Fe to the amount of Si (Fe amount / Si amount) at the point where the Fe amount in the second oxide layer was maximum was 11. The ratio of the amount of Fe to the amount of Si (Fe amount / Si amount) at the point where the Si amount in the third oxide layer was maximum was 1.6. The ratio of the amount of Fe to the amount of Si (Fe amount / Si amount) at the point where the Fe amount in the fourth oxide layer was maximum was 25.

[0065] In FIG. 3, the portion from the starting point to the first boundary b1 where the Fe content and the Si content are reversed is an alloy particle 10. The first oxide layer 20 extends from the first boundary b1 to a second boundary b2 which is the midpoint between the point P1 where the Si content is at its maximum value and the point P2 where the Fe content is at its maximum value. The second oxide layer 30 extends from the second boundary b2 to a third boundary b3 which is the midpoint between the point P2 where the Fe content reaches its maximum value and the point P3 where the Si content reaches its maximum value. The third oxide layer 40 extends from the third boundary b3 to a fourth boundary b4 which is the midpoint between the point P3 where the Si content reaches its maximum value and the point P4 where the Fe content reaches its maximum value. The fourth oxide layer 50 extends from the fourth boundary b4 to a fifth boundary b5, which is the point where the O amount is 34% of the maximum value.

[0066] Furthermore, from the FFT image, which was a Fourier transform of the STEM image, it was confirmed that the first oxide layer was amorphous, the second oxide layer was crystalline, the third oxide layer was amorphous, and the fourth oxide layer was crystalline.

[0067] [Measurement of voltage resistance performance] The voltage resistance performance was measured in the thickness direction of the ring. The measurement was performed using a digital ultra-high resistance / micro ammeter (Advantest R8340A), with the ring clamped between the attached probes and the resistance value [Ω] recorded when a specified voltage was applied. The applied voltage was set to a resistance value of 10 5 The resistance was swept from 1V to 10V in 1V increments, and from 10V to 1000V in 10V increments until the resistance fell below 10 5 The applied voltage [V] just before it fell below [Ω] was recorded, and the electric field strength [V / mm] was calculated by dividing the thickness of the ring by this voltage. The results are shown in Table 1. In addition, even at the maximum applied voltage of 1000V, the resistance value was 10 5 If the resistance value does not fall below [Ω], it is recorded in Table 1 as being equal to or greater than the resistance value [Ω] at 1000 V divided by the ring thickness.

[0068] [Measurement of relative permeability] After impregnating the ring with epoxy resin to improve its mechanical strength, the relative permeability was measured using an impedance analyzer (Keysight E4991A). The relative permeability was measured at 1 MHz. The results are shown in Table 1.

[0069] [Measurement of DC bias characteristics] Furthermore, a copper wire with a diameter of 0.35 mm was wound 24 times around the ring, and the DC superposition characteristics were measured using an LCR meter (Keysight 4284A). A DC current of 0 to 30 A was applied to the copper wire, and the relative permeability (μ value) was calculated from the obtained L value, and the current value (Isat@-20%) at which the μ value decreased to 80% of the initial value was obtained. From Isat@-20%, the ring size, and the number of turns of the copper wire, Hsat@-20% [kA / m], which is the magnetic field at which the μ value becomes 80% of the initial value, was calculated. The results are shown in Table 1. Incidentally, a copper wire wound around a ring also constitutes the inductor of the present invention.

[0070] (Examples 2 and 3) Except for changing the pressure for molding the coated particles to 300 MPa and 100 MPa, rings were produced in the same manner as in Example 1, and the electric field strength, resistance value, relative permeability, and Hsat@-20% were measured. The results are shown in Table 1.

[0071] (Comparative Examples 1 to 3) A ring was produced in the same manner as in Examples 1 to 3, except that raw material particles were used instead of the coated film-forming particles, and the electric field strength, resistance value, relative permeability, and Hsat@-20% were measured. The results are shown in Table 1.

[0072] [Table 1]

[0073] The results in Table 1 show that the metal magnetic particles of the present invention have a higher electric field strength and are superior in voltage resistance compared to Comparative Examples 1 to 3, which do not have coated film-formed particles.

[0074] Furthermore, the relationship between Hsat@-20% [kA / m] (vertical axis) and relative magnetic permeability (horizontal axis) in each of the examples and comparative examples is shown in Figure 4. It was confirmed from Figure 4 that the plot position of the metal magnetic particles according to Examples 1 to 3 is shifted to the upper right side compared to the metal magnetic particles according to Comparative Examples 1 to 3. From this, it can be confirmed that when the relative magnetic permeability is approximately the same, the value of Hsat@-20% tends to improve, and it is understood that the metal magnetic particles of the present invention have excellent DC superposition characteristics. [Explanation of symbols]

[0075] 1 Metal magnetic particles 10 Alloy particles 20 First oxide layer 30 Second oxide layer 40 Third oxide layer 50 4th oxide layer b1 first boundary b2 second boundary b3 third boundary b4 4th boundary b5 5th boundary The point where the amount of P1 and P3Si reaches a maximum The point where the amount of P2 and P4Fe reaches its maximum value

Claims

1. A metal magnetic particle having an oxide layer provided on the surface of an alloy particle containing Fe and Si, the oxide layer has, from the alloy particle side, a first oxide layer, a second oxide layer, a third oxide layer, and a fourth oxide layer, In a line analysis of elemental content using scanning transmission electron microscopy-energy dispersive X-ray analysis, the first oxide layer is a layer in which the amount of Si has a maximum value, the second oxide layer is a layer in which the Fe amount has a maximum value, the third oxide layer is a layer in which the amount of Si has a maximum value, the fourth oxide layer is a layer in which the Fe amount has a maximum value, A metal magnetic particle, characterized in that the maximum value of the Si content in the first oxide layer is greater than the maximum value of the Si content in the third oxide layer.

2. 2. The metal magnetic particle according to claim 1, wherein the weight ratio of Si in the alloy particle is 1.5 parts by weight or more and 8.0 parts by weight or less per 100 parts by weight of the total weight of the Fe and the Si.

3. 3. The metal magnetic particle according to claim 1, wherein the alloy particle contains less than 1.0 part by weight of Cr per 100 parts by weight of the total weight of the Fe and the Si.

4. A metal magnetic particle having an oxide layer provided on the surface of an alloy particle containing Fe and Si, the oxide layer has, from the alloy particle side, a first oxide layer, a second oxide layer, a third oxide layer, and a fourth oxide layer, In a line analysis of elemental content using scanning transmission electron microscopy-energy dispersive X-ray analysis, the first oxide layer is a layer in which the amount of Si has a maximum value, the second oxide layer is a layer in which the Fe amount has a maximum value, the third oxide layer is a layer in which the amount of Si has a maximum value, the fourth oxide layer is a layer in which the Fe amount has a maximum value, The metal magnetic particle, wherein the third oxide layer has a Fe content greater than a Si content.

5. A metal magnetic core, characterized in that metal magnetic particles described in any one of claims 1 to 4 are joined to each other by the oxide layer.

6. An inductor comprising the metal magnetic particle according to any one of claims 1 to 4 or the metal magnetic core according to claim 5.

Citation Information

Patent Citations

  • JP1973066971A

  • JP1975082002A

  • Magnetic material, electronic component, and manufacturing method of magnetic material

    JP2019009307A

  • Soft magnetic metal powder, powder magnetic core and magnetic component

    JP2019160943A